The economics of defense in the nuclear age - Hitch, Charles Johnston; McKean, Roland N. (Cambridge, Harvard University Press, 1960)
The purpose of this book is to explain a way of looking at military problems in: (1) The resources available for defense. (2) Efficiency in using defense resources. (3) Special problems and applications.
Including bibliographical references: p. [407]-418.
ne 17/05/2018
Loan
Keywords: United States; United States